RELATIONSHIP BETWEEN WORK DURATION, LENGTH OF WORK, AND SLEEP DURATION WITH WORK FATIGUE AMONG ONLINE TAXI BIKE DRIVERS IN GREATER JAKARTA - Surury, Istianah; Aisya Alawiyah; Fitri Anggraeni; Vicky Abiansyah; Nastiti Dyah Prastiwi (Journal of Vocational Health Studies, 2024)
Background: Online taxi bike drivers were part of the road users vulnerable to accidents due to a demand that required online taxi bike drivers to work on the highway. Work duration, length of work, and sleep duration could cause the fatigue experienced by online taxi bike drivers. Purpose: See the strength of the relationship between work duration, length of work, sleep duration and work fatigue among online taxi bike drivers in Greater Jakarta. Method: This study was observational with a cross-sectional design involving as many as 52 online taxi bike drivers selected by non-probability sampling from online taxi bike drivers in Greater Jakarta from the end of November 2022 to early December 2022. Result: The majority of respondents (84.6%) were under 40 years old, male (92.3%), worked more than eight hours a day (55.8%), had experience as online taxi bike drivers for more than 3 years (73.1%), sleep duration less than 8 hours (78.8%), and there were 36 online taxi bike drivers (69.2%) reported experiencing high-very high levels of fatigue. The work duration is significantly related to work fatigue (p-value = 0.002). Also, there was no significant relationship between the length of work (p-value = 0.268) and sleep duration (p-value = 0.058) with work fatigue. Conclusion: There was a significant relationship between work duration and work fatigue, and there was no significant relationship between the length of work and sleep duration with work fatigue. The taxi drivers with work duration >8 hours, length of work >3 years, and sleep duration <8 hours had higher risk factors for work fatigue. If a taxi bike driver works more than 8 hours daily, it is advisable to compensate with adequate rest.